Score Associated with the Outcome after Multiple Ablation Procedures in Patients with Atrial Fibrillation. Issue 6 (5th February 2014) - WÓJCIK, MACIEJ; BERKOWITSCH, ALEXANDER; ZALTSBERG, SERGEY; HAMM, CHRISTIAN W.; PITSCHNER, HEINZ F.; KUNISS, MALTE; NEUMANN, THOMAS
<x xml:space="preserve">Abstract</x> Background Catheter ablation (CA) of atrial fibrillation (AF) is now established therapeutic option. Multiple procedures (MPs) are often needed to achieve the satisfactory outcome. The aim of the study was to assess the outcome after MPs in AF patients categorized to risk‐score groups. Methods We followed a cohort of consecutive 911 (69% male; median 59 years) patients with AF (58% paroxysmal) who had CAAF performed. ALARMEC (Atrial fibrillation type, Left Atrium size, Renal insufficiency, MEtabolic syndrome, cardiomyopathy) risk score was calculated for each patient. The end point was maintenance of sinus rhythm at the follow‐up of 60 months. Results We performed 1, 199 CAAF procedures. One, two, and three procedures were performed in 663 (73%), 208 (23%), and 40 (4%) patients, respectively. Outcome after the first procedure (56%) was improved with MPs (76%). MPs > 2 were performed in 1%, 3%, 5%, 6%, and 10% patients with ALARMEC score of 0, 1, 2, 3, and 4, respectively. MPs were successful in 89%, 86%, 81%, 65%, and 43% of patients with ALARMEC score of 0, 1, 2, 3, and 4, respectively. Outcome in 174 (19%) patients on antiarrhythmic drugs (AADs) was 85%, 68%, 75%, 44%, and 39% in ALARMEC score: 0, 1, 2, 3, and 4, respectively. Outcome in 737 (81%) patients without AAD was 90%, 85%, 80%, 77%, and 69% in ALARMEC score of 0, 1, 2, 3, and 4, respectively. Conclusion The moderate success rate after index procedure of CAAF can be further improved with multiple ones and AAD.